Silver–polysaccharide antimicrobial nanocomposite coating for methacrylic surfaces reduces Streptococcus mutans biofilm formation in vitro. Issue 12 (December 2015) - Ionescu, A.C.; Brambilla, E.; Travan, A.; Marsich, E.; Donati, I.; Gobbi, P.; Turco, G.; Di Lenarda, R.; Cadenaro, M.; Paoletti, S.; Breschi, L.
Graphical abstract: Abstract: Objectives: The aim of this study was to determine the in vitro microbiological performances of a lactose-modified chitosan (Chitlac) coating inside which silver nanoparticles were embedded (Chitlac-nAg) for BisGMA/TEGDMA methacrylic specimens. Methods: Different concentrations of nAg inside Chitlac coating were tested (1 mM, 2 mM, 5 mM). Specimen surface was analyzed by means of field-emission scanning electron microscopy (FEISEM) and energy-dispersive X-ray spectroscopy (EDS). A 48 h monospecific Streptococcus mutans biofilm was developed over the specimen surfaces using a modified drip-flow bioreactor; adherent viable biomass was assessed by MTT test and biofilm was imaged by confocal laser-scanning microscopy (CLSM). Results: The presence of finely dispersed nanoparticles inside the Chitlac coating was confirmed by FEISEM and EDS analysis. All nanoparticles were embedded in the Chitlac coating layer. Chitlac-nAg coatings were able to significantly decrease biofilm formation depending on the nAg concentration, reaching a −80% viable biomass decrease when the 5 mM nAg-Chitlac group was confronted to non-coated control specimens. CLSM analysis did not provide evidence of a contact-killing activity, however the antibacterial Chitlac-nAg coating was able to alter biofilm morphology preventing the development of mature biofilm structures. Conclusions: The microbiological model applied in this study helped in assessing the antibacterial properties of a coating designed for methacrylate surfaces. Clinical significance: A microbiological model based on a bioreactor-grown biofilm is useful for preliminary in vitro tests of dental materials. In translational terms, an antibacterial nanocomposite coating based on Chitlac-nAg and designed to be applied to methacrylic surfaces may be a promising way to obtain dental materials able to actively prevent secondary caries.